2011
DOI: 10.1088/0741-3335/53/5/054008
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of turbulence with magnetic islands: effect on bootstrap current

Abstract: Abstract.A finite radial temperature gradient has been observed to be maintained within magnetic islands in gyro-kinetic turbulence simulations despite the fast motion along the field, and is related to the trapped particles which do not move along the field around the island. Recent calculations of the interaction of drift wave turbulence with magnetic islands have shown that turbulence can exist within the separatrix, which in turn allows only the partial flattening of electron temperature profiles. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 29 publications
(57 reference statements)
1
36
0
Order By: Relevance
“…This implies that one needs to consider the parallel gradient of the electron pressure in Eq. (14), which becomes which, after integration, yields…”
Section: A Frozen Electrons Inside the Islandmentioning
confidence: 98%
“…This implies that one needs to consider the parallel gradient of the electron pressure in Eq. (14), which becomes which, after integration, yields…”
Section: A Frozen Electrons Inside the Islandmentioning
confidence: 98%
“…Here, we briefly review gyrokinetic simulation studies on interactions between the ITG turbulence and magnetic islands and on basic physics of magnetic reconnection. Most gyrokinetic studies on the interaction of turbulence with magnetic islands consist of carrying out electrostatic simulations in the presence of a fixed magnetic island (Poli et al 2009;Hornsby et al 2011Hornsby et al , 2012Waltz and Waelbroeck 2012), and it is reported that the production of long wavelength mode by ITG turbulence can give rise to an oscillating vortex flow inside the island separatrix (Hornsby et al 2011), and the oscillation is related to the geodesic acoustic mode (Hornsby et al 2012). The momentum transport associated with a magnetic island interacting with external magnetic perturbation is also studied (Waltz and Waelbroeck 2012).…”
Section: Magnetic Islands and Magnetic Reconnectionmentioning
confidence: 99%
“…However, we have verified the statements made in this section using a reduced model in which both radial diffusion as well as collisions are kept. The results of this model will be published elsewhere [33].…”
Section: Finite Electron Temperature Gradient and Bootstrap Currentmentioning
confidence: 99%